1994
DOI: 10.1007/bf00202821
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry of SINE-R.C2 a human-specific retroposon

Abstract: We have reported previously that a retroposon, containing a variable number of tandemly repeated nucleotide sequences, is present in the third intron of the human C2 gene. This element, termed SINE-R.C2, is a member of a large retroposon family derived from the endogenous retrovirus HERV-K10 and estimated to include a few thousand copies per haploid human genome. In the present study we analyzed genomic DNA from 175 humans from several ethnic groups including Americans of European and African descent, Chinese,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…Retroelements like solitary LTRs contribute to allelic variation in contemporary populations, as has been shown in the complement and HLA loci (51,53). They can also serve as useful markers to study the evolution of those genes in the primate lineage (62,63).…”
Section: Htdv/herv-k a Family Coding For Viral Particlesmentioning
confidence: 98%
“…Retroelements like solitary LTRs contribute to allelic variation in contemporary populations, as has been shown in the complement and HLA loci (51,53). They can also serve as useful markers to study the evolution of those genes in the primate lineage (62,63).…”
Section: Htdv/herv-k a Family Coding For Viral Particlesmentioning
confidence: 98%
“…Using the bioinformatic tool, we examined that a schizo-cDNA clone derived from the postmortem tissue of the frontal cortex of an individual suffering from schizophrenia (GenBank, accession no. AA772777) was found to have sequences showing a high degree of homology to the SINE-R.C2 (Zhu et al, 1994). Therefore, we designed PCR primers from the schizophrenic brain cDNA.…”
Section: Resultsmentioning
confidence: 99%
“…SINE-R retroposons were amplified by the primer pair JS902 (5'-GAGAATGGGCCATGATG-AC-3', bases 4-22) and JS9O3 (5'-GATCATTCTTGG-ATGTTTCT-3', bases 466-485) from schizophrenic brain Sll cDNA clone (GenBank, accession no. AA772777), which has a high level of sequence homology with SINE-R.C2, 11, 14, 19, and HS307/ HS408 elements (Ono et al, 1987;Zhu et al, 1994;Kim et al, 1999b). The PCR conditions were those of Kim et al (1996) with an annealing temperature of 56°C.…”
Section: Pcr Amplification For Sine-r Retroposonsmentioning
confidence: 99%
See 1 more Smart Citation
“…chromosomal changes in the genome? We have reported that the SINE-R.C2, a human specific retroposon (Zhu et al, 1994) that was derived from the HERV-K sequence, has close homologies with two sequences (HS307 and HS408) within the Xq21.3 block of that transposed to the Y chromosome sometime after the separation of the human and chimpanzee lineages (Kim et al, 1999b), and that a number of similar elements are present on the 7, 17, and Y chromosomes Crow, 1999, 2000) and in the African great apes (Kim et al, 1999c). This retroposon may therefore represent a family that has been active in recent human evolution.…”
Section: Introductionmentioning
confidence: 99%